Rwanda - Education Country Status Report : Toward Quality Enhancement and Achievement of Universal Nine Year Basic Education - An Education System in Transition; A Nation in Transition - World Bank (World Bank, 2012)
The Republic of Rwanda is a relatively small country located in Central Africa with a population of approximately 10 million people, making it one of the more densely populated countries in the world. The current government is taking positive steps to helps the country emerge from its tragic past, and aims to promote reconciliation and unity among all Rwandese and forbids any political activity or discrimination based on race, ethnicity, or relation. The government's effort to deliver basic public services to its population, including education, also follow the spirit of inclusiveness and aims to diminish gender, socioeconomic and geographic disparities. Rwanda's development agenda is entering a new phase as it transitions from post-genocide recovery to producing a population that is regionally and globally competitive and economically and socially secure. The education sector plays a significant role in fulfilling the national agenda. This Country Status Report (CSR) takes stock of recent progress and identifies a new generation of challenges facing the education sector, particularly in the context of ongoing decentralization and the government's recent initiative to extend basic education to nine years of schooling.